Prebiotic carbohydrates modify the mucosa associated microflora of the human large bowel. Issue 11 (11th October 2004) - Langlands, S J; Hopkins, M J; Coleman, N; Cummings, J H
Abstract : Background and aims: The mucosa associated flora of the large intestine is important in determining mucosal function although what controls its composition is unknown. This study has determined the effect of the prebiotic carbohydrates oligofructose and inulin on the mucosal flora. Methods: An in vitro chemostat model of both planktonic and surface associated bacteria was used followed by an intervention study in 29 subjects undergoing colonoscopy. Subjects: Fourteen subjects, recruited from colonoscopy waiting lists, supplemented their diet for two weeks with a mix of 7.5 g of oligofructose and 7.5 g inulin. Fifteen subjects were recruited at the time of colonoscopy and given no supplement. Multiple endoscopic biopsies were taken from the caecum, transverse and descending colon, and rectum. The mucosal flora was characterised by culture and to species level by cellular fatty acid profiles. Cell proliferation was assessed by immunohistochemical staining for minichromosome maintenance protein 2, Ki67, and proliferating cell nuclear antigen. Results: In vitro prebiotics increased surface counts of bifidobacteria from 6.6 to 7.3 log10 colony forming units (CFU) per slide (p<0.0006) with no significant changes in planktonic bacteria. In the feeding study, prebiotics increased mucosal bifidobacteria (log CFU/g mucosa (SEM)) in both the proximal (control 5.3 (0.4) v prebiotic 6.3 (0.3)) (p = 0.059) and distal (control 5.2 (0.3) v prebiotic 6.4 (0.3)) colon (p = 0.01). Lactobacilli were also increased (3.0 (0.1) v 3.7 (0.2) (p = 0.02) in the proximal and 3.1 (0.1) v 3.6 (0.2) (p = 0.04) in the distal colon, respectively). There were significantly more eubacteria in fed subjects but no changes in total anaerobes clostridia, bacteroides, or coliforms, nor in proliferation indices. Conclusion: Prebiotic carbohydrates can change the composition of the mucosa associated flora significantly.